THE GREATER OMENTUM IN WOMEN WITH OVARIAN CANCER - L. V. Khalikova (Креативная хирургия и онкология)
A comparative study of the greater omentum 60 healthy  women and 40 patients with ovarian  cancer  has done.  Found that  when  the  disease  omentum reduced in size, density decreases and size of lymphoid  elements. This morphological pattern indicates  a decrease in the immune  properties of the greater omentum.